Influence of Hydration on Proton Transfer in the Guanine-Cytosine Radical Cation (G(•+)-C) Base Pair: A Density Functional Theory Study - Kumar, Anil (2009)
On one-electron oxidation all molecules including DNA bases become more acidic in nature. For the GC base pair experiments suggest that a facile proton transfer takes place in the G(•+)-C base pair from N(1) of G(•+) to N(3) of cytosine. This intra-base pair proton transfer reaction has been extensively considered using theoretical methods for the gas phase and it is predicted that the proton transfer is slightly unfavorable in disagreement with experiment. In the present study, we consider the effect of the first hydration layer on the proton transfer reaction in G(•+)-C by the use of density functional theory (DFT), B3LYP/6-31+G** calculations of the G(•+)-C base pair in the presence of 6 and 11 water molecules. Under the influence of hydration of 11 waters, a facile proton transfer from N(1) of G(•+) to N(3) of C is predicted. The zero point energy (ZPE) corrected forward and backward energy barriers, for the proton transfer from N(1) of G(•+) to N(3) of C, was found to be 1.4 and 2.6 kcal/mol, respectively. The proton transferred G(•)-(H(+))C + 11H(2)O was found to be 1.2 kcal/mol more stable than G(•+)-C + 11H(2)O in agreement with experiment. The present calculation demonstrates that the inclusion of the first hydration shell around G(•+)-C base pair has an important effect on the internal proton transfer energetics.